Analysis of final semester assessment questions (PAS) in grade XI chemistry online learning based on cognitive domain level of revised Bloom's taxonomy - Tika Reformatika Fuadi; Evi Sapinatul Bahriah; Salamah Agung (Pascasarjana Universitas Negeri Medan, 2022)
This study aims to determine the distribution of cognitive domain levels from Final Semester Assessment (PAS) questions in online learning chemistry grade XI based on the cognitive domain of Revised Bloom's Taxonomy. The method used is descriptive method with the instrument in the form of a check-list format. The object of this research is the question of PAS chemistry grade XI even semester in four schools in South Tangerang City. The data were obtained through analysis of the cognitive domain level of Revised Bloom's Taxonomy on each item and validated through triangulation techniques by two experts in the field of chemistry. The results showed each of the percentages for the C1 domain is 24.3%, the C2 domain is 32.9%, the C3 domain is 32.1%, the C4 domain is 10.7%, and the C5 and C6 domain are both 0%. This show that the distribution of cognitive domains on the chemistry PAS questions for grade XI was not evenly distributed, PAS questions were distributed in four domains out of a total of six cognitive domains, C1, C2, C3, and C4. There are no questions in the cognitive domains of C5 and C6.Keywords:Chemistry online learning, Final semester assessment, Question analysis, Revised Bloom’s taxonomy